Anti-obesity and antihyperlipidemic effects of Phaleria macrocarpa fruit liquid CO2 extract: In vitro, in silico and in vivo approaches - Mia, Md. Abdur Rashid; Ahmed, Qamar Uddin; Ferdosh, Sahena; Helal Uddin, A.B.M.; Hejaz Azmi, Syed Najmul; Ammar Al-Otaibi, Fatimah; Parveen, Humaira; Mukhtar, Sayeed; Ahmed, Mohammad Z.; Sarker, Md. Zaidul Islam (Elsevier, 2023)
Objective: Phaleria macrocarpa fruit has been reported to be effectively used in Malaysia and neighboring countries to prevent obesity. Despite its anti-obesity potential, no research has ever predicted the compound-lipase, compound-HMG-CoA reductase interactions and in vivo investigations to further confirm its anti-obesity properties. Thus, the purpose of this study was to assess the anti-obesity and antihyperlipidemic effects of P. macrocarpa by in vitro, computational (in silico), and in vivo assays. Method: Initially, fruit was extracted through liquid CO2 and heating under reflux extraction methods to obtain liquid CO2 extracts (LCE-1 and LCE-2) and heating under reflux extract (HRE), respectively. Subsequently,allthreeextractswereassessedforantioxidantpotentialsthroughinvitrobioassaysand FTIRanalysistoidentifydifferenttypesoffunctionalgroupspresentintheexistingbioactivecompounds. Successively,themostactivefraction(LCE-2)wassubjectedtoGCMSanalysisfortheidentificationof lipidloweringandlipaseinhibitorsthroughmoleculardockingapproach.Finally,anti-obesityandlipid loweringeffectswerefurtherconfirmedthroughaninvivoassayusingmice. Result:LCE-2exhibitedhigherDPPH(IC50=0.172mg/mL)andFRAP(78.98AAEmg/g)antioxidantactivitiesandshowedmorepotentpeaksinFTIRchromatogramsthanLCE-1andHRE.Amongtheidentified tentativebioactivecompoundsviz.methylpalmitate,palmiticacid,ethylpalmitate,methyloleate,oleic acid,cis-vaccenicacid,3-deoxyestradiolandphenol,2,20-methylenebis[6-(1,1-dimethylethyl)-4-methylwerefoundasananti-obesityandlipidloweringcompoundswhoseprotein–ligandinteractionwasconfirmedbybindingaffinity,aminoacidresiduesandbondinginteractions.Similarly,anti-obesityandlipid loweringfindingswerealsofoundinamicemodelafter6weekstreatmentatadoseof250mg/kgb.w. Conclusion:Basedontheaforementionedinvitro,insilicoandinvivofindings,itisconcludedthatthe LCE-2possesseslipaseandHMG-CoAreductaseinhibitorsthatcanassisttodevelopthisplant’sextract asanalternativesafelipidloweringherbalmedicineinfuture.